Virtual Learning Media Exploration 3D View of the Konto River Watershed to Support 21st Century Learning - Feri Fahrian Maulana; Ifan Deffinika; Fatimatun Jazilah; Leela Balab Pokhrel (JAMBURA GEO EDUCATION JOURNAL, 2023)
21st-century learning has encouraged more interactive learning. The use of technological media in geography learning continues to be developed. However, the development of 3D view virtual exploration media is still rarely carried out. This research discusses virtual exploration of 3D view which can carry out direct 3-dimensional interactions to give students a better impression in learning geography. This research aims to provide innovation in developing Virtual Exploration as a learning media to support 21st-century learning in realizing environment-based learning. The research method used is R and D with the ADDIE model consisting of Analyst, Design, Development, Implementation, and Evaluation. The Development Phase is carried out in accordance with the research objectives. Data was collected using a mixed questionnaire consisting of (1) a closed questionnaire in the form of an answer checklist and (2) an open questionnaire in the form of direct answers from respondents. The data analysis technique used is the results of initial analysis data, data from material and media validity tests as well as student and teacher response data to the media. The media validation results were carried out by material experts with a percentage value of 90.50%, media experts at 84.5%, and geography teachers at 91.50%. The average student response from the media was 88.65%. Thus, the 3D view virtual exploration learning media on the sub-terrestrial hydrosphere material of the Konto watershed has the potential to be an effective learning tool in schools and gets a very positive response from students.